2012
DOI: 10.1111/j.1540-8175.2012.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Atrial Function in Hypertrophic Cardiomyopathy and Athlete's Heart: A Left Atrial Myocardial Deformation Study

Abstract: LA myocardial deformation is significantly impaired in patients with HCM compared to athletes and healthy controls. LA strain and strain rate assessed by 2D speckle tracking should be incorporated in the evaluation of trained athletes with LVH and LA dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 34 publications
(49 reference statements)
2
49
2
1
Order By: Relevance
“…A recent study found that while a majority of endurance athletes had LA strains similar to controls, a subgroup was characterized by impaired strain, and suggested that this subgroup may operate at higher LA wall stress (Gabrielli et al 2014). Conversely, our data and others have demonstrated enhanced or preserved atrial strain following both short-and long-term endurance training (Gabrielli et al 2012), while LA strain is depressed in patients with hypertrophic cardiomyopathy (Gabrielli et al 2012). Thus it is possible that early in training, LA strain increases acutely with loading, before structural remodeling occurs and strain normalizes with prolonged endurance training.…”
Section: Myocardial Deformation Mechanicsmentioning
confidence: 59%
“…A recent study found that while a majority of endurance athletes had LA strains similar to controls, a subgroup was characterized by impaired strain, and suggested that this subgroup may operate at higher LA wall stress (Gabrielli et al 2014). Conversely, our data and others have demonstrated enhanced or preserved atrial strain following both short-and long-term endurance training (Gabrielli et al 2012), while LA strain is depressed in patients with hypertrophic cardiomyopathy (Gabrielli et al 2012). Thus it is possible that early in training, LA strain increases acutely with loading, before structural remodeling occurs and strain normalizes with prolonged endurance training.…”
Section: Myocardial Deformation Mechanicsmentioning
confidence: 59%
“…In another study by Sun et al demonstrated that all components of LA-SR in the hypertensive group were significantly lower than in athletes and normal controls (40) . Previous study showed that LA-S and SR were significantly decreased in patients with HCM than in highly trained athletes and healthy controls and provided valuable additional information to that obtained by conventional echocardiography in the differential diagnosis between pathological and physiological LVH (28) . Moreover, recent studies have found pathological LVH in long-term AAS users.…”
Section: Discussionmentioning
confidence: 95%
“…The physiological hypertrophy that occurs in athletes is associated with increased ventricular mass, normal organization of cardiac structure, and no increase in collagen content. On the other side, the hypertrophy observed in AAS using bodybuilders is characterized by myofibrillar disarray and collagen accumulation, eventually leading to systolic and diastolic dysfunction (27,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Nach dieser Zeit beginnt jedoch die Rückbildung der antrainierten Hypertrophie und führt bereits nach 8 Wochen zu signifikanten Dimensionsverminderungen und zur Reduzierung der Werte kardialer Funktionsmessungen, wie der Verkürzungsfraktion (FS) und des Herzzeitvolumens (Kriz et al 2000). Auch Gewebedopplermessungen zeigten beim Menschen trainingsbedingte Veränderungen (Caso et al 2000, Vinereanu et al 2001, D'Andrea et al 2001und 2010, Poulsen et al 2007, Gabrielli et al 2012 …”
Section: Introductionunclassified